Atrophic pseudarthrosis of humeral diaphyseal fractures: medico-legal implications and methodological analysis of the evaluation. - Basile, Giuseppe; Avato, Franco Maria; Passeri, Alberto; Accetta, Riccardo; Amadei, Federico; Giorgetti, Arianna; Castoldi, Daniele; Fozzato, Stefania (Acta Biomedica Atenei Parmensis, 2022)
Humeral shaft fractures account for 1- 3% of all fractures and about 20-27% of those involving the humerus. In the past they were often conservatively treated, with an acceptable consolidation rate. Open reduction and internal fixation (ORIF) is the best choice in polytrauma patients, in complex or pathological fractures and in those associated with vascular injuries. Regardless the type of fixation used, these fractures can evolve into delayed union or pseudarthrosis (PSA). It should be noted that the humeral shaft itself has a high intrinsic healing potential, due to the blood supply provided by the surrounding muscles. The aim of this work is to evaluate whether the causes that led to the development of atrophic pseudarthrosis in a humeral diaphyseal fracture are attributable to inadequate management of this fearful complication and to highlight the possible medico-legal repercussions. We will try to verify whether the currently used forensic evaluation parameters of permanent disability are appropriate and adequate in relation to the complexity of such injuries. This complexity also includes the repercussions on the ergonomic efficiency of the entire limb, the relative possible postural alterations, the inevitable extension of the period of traumatic illness and the relative repercussions on the overall compromised structure of the subject.